Treading a tightrope: A rhetorical study of the tension between the executive and collective leadership of the African National Congress (ANC): From Nelson Mandela to Thabo Mbeki - Ngesi, Sifiso Eric (Centre for Rhetoric Studies, 2014)
Includes bibliographical references.